World trade patterns and prices: The role of productivity and quality heterogeneity - Cristiana Benedetti Fasil; Teodora Borota (Uppsala University, Department of Economics, 2010)
This paper analyzes the role of product quality and labor efficiency in shaping the trade patterns and trade intensities within and across two groups of countries, the developed and richer North and the developing South. Taking prices as a proxy for quality, recent empirical literature identifies a positive relation between income per capita and both export and import prices, suggesting that rich countries trade goods of relatively higher quality. Instead of relying on specific demand side mechanisms such as non-homothetic preferences, we focus on the North-South differences in technology. We employ a four country North-South trade model with two dimensions of firm heterogeneity. Differences in firms'; product qualities and cost efficiencies result in a price distribution generating different consumption bundles and the observed export and import prices across rich and poor countries. Furthermore, the resulting total expenditure allocation across quality shows that the North (South) spends a larger share of its income on high (low) quality even with the same homothetic preferences across regions.
urn:nbn:se:uu:diva-122711
Keywords: F10; F12; F14; L11; L15; 330; international trade patterns; North-South trade; import and export prices; heterogeneous firms; product quality; Internationale Wirtschaftsbeziehungen; Nord-Süd-Beziehungen; Außenhandelspreis; Produktqualität; Verbraucherausgaben; Theorie